Policing the open road: how cars transformed American freedom - Seo, Sarah A. (Harvard University Press, 2019)
Policing the Open Road examines how the rise of the car, that symbol of American personal freedom, inadvertently led to ever more intrusive policing--with disastrous consequences for racial equality in our criminal justice system. When Americans think of freedom, they often picture the open road. Yet nowhere are we more likely to encounter the long arm of the law than in our cars. Sarah Seo reveals how the rise of the automobile transformed American freedom in radical ways, leading us to accept--and expect--pervasive police power. As Policing the Open Road makes clear, this expectation has had far-reaching political and legal consequences.--